2016
DOI: 10.1089/hum.2016.016
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral Vector-Mediated Correction of a Mouse Model of Leukocyte Adhesion Deficiency Type I

Abstract: Leukocyte adhesion deficiency type I (LAD-I) is a primary immunodeficiency caused by mutations in the ITGB2 gene and is characterized by recurrent and life-threatening bacterial infections. These mutations lead to defective or absent expression of β2 integrins on the leukocyte surface, compromising adhesion and extravasation at sites of infection. Three different lentiviral vectors (LVs) conferring ubiquitous or preferential expression of CD18 in myeloid cells were constructed and tested in human and mouse LAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
3
16
0
1
Order By: Relevance
“…34 Our study included a wide distribution of VCN (ranging from 0.3 to 9.8). While these VCNs are in line with previous studies from our group and others [36][37][38] it is expected that lower VCNs would be observed in the clinical application based on our previous studies in human CD34+ cells, 23 and clinical trials in other therapeutic areas. 34,39 Unfortunately, no published data is available regarding the protection from the infections in clinical trials with lentiviral vectors encoding for gp91phox.…”
Section: Discussionsupporting
confidence: 91%
“…34 Our study included a wide distribution of VCN (ranging from 0.3 to 9.8). While these VCNs are in line with previous studies from our group and others [36][37][38] it is expected that lower VCNs would be observed in the clinical application based on our previous studies in human CD34+ cells, 23 and clinical trials in other therapeutic areas. 34,39 Unfortunately, no published data is available regarding the protection from the infections in clinical trials with lentiviral vectors encoding for gp91phox.…”
Section: Discussionsupporting
confidence: 91%
“…107 More recently, the canine (canine LAD [CLAD]) and murine models of disease have been successfully treated using HSCs transduced with either foamy or lentiviral vectors expressing CD18. 108,109 In many of these conditions, preclinical efficacy and safety studies using improved viral vectors, including vector platforms developed from other classes of retrovirus such as foamy and avian viruses (which may have enhanced safety in terms of genotoxicity), are currently being undertaken in order to determine clinical applicability.…”
Section: Preclinical Development Of Gene Therapy For Other Candidate mentioning
confidence: 99%
“…Our studies showed the efficacy and safety of a gene therapy approach in an LAD‐I mouse model using a SIN‐LV in which a chimeric internal promoter—already used in the gene therapy of X‐CGD patients—drives the expression of CD18. The Chim.hCD18‐LV conferred phenotypic correction in mouse LAD‐I leukocytes, which then expressed the heterodimer in their membrane and migrated to inflamed sites . Based on these experimental results it is expected that LAD‐I will be added to the list of PIDs successfully treated by gene therapy.…”
Section: Gene Therapy In Primary Immunodeficienciesmentioning
confidence: 93%
“…A very low and transient engraftment of corrected cells was observed in this trial, probably due to the absence of patient's conditioning and to the fact that corrected LAD‐I progenitor cells do not develop proliferative advantage. Recent experimental data have raised expectations for gene therapy in these patients. Our studies showed the efficacy and safety of a gene therapy approach in an LAD‐I mouse model using a SIN‐LV in which a chimeric internal promoter—already used in the gene therapy of X‐CGD patients—drives the expression of CD18.…”
Section: Gene Therapy In Primary Immunodeficienciesmentioning
confidence: 99%